Treatment Strategy in Atrial Tachycardia Originating From the Atrial Appendage - Hai-Yang, Xie; Zi-Cong, Feng; Xiao-Gang, Guo; Qi, Sun; Jian-Du, Yang; Jian, Ma (Frontiers in Physiology, 2022)
Background: Atrial appendage tachycardia (AAT) originating from the atrial appendage (AA) was the most difficult to eliminate by radiofrequency catheter ablation (RFCA). The optimal management strategy for AAT refractory to RFCA remains unclear. Objective: To investigate the long-term result of ablative therapy and the optimal alternative managements for AAT refractory to RFCA. Methods: Fifty-one (8.7%) patients with AAT originating from the atrial appendage undergoing RFCA were recruited. Video-assisted atrial appendectomy and oral ivabradine were applied to those AATs refractory to RFCA and to evaluate their safety and long-term efficacy. Results: We included 51 (8.7%) patients with 51 AATs confirmed by activation mapping and contrast venography, of which 28 (54.9%) AATs originated from the distal AA. Fourteen (27.4%) AATs, including 13 originated from the distal AA and 1 arising from the proximal AA, were refractory to RFCA. Ten of 11 (90.9%) AATs originated from the distal AA were eliminated after atrial appendectomy and the other 3 AATs were suppressed using oral ivabradine. Origin at the distal AA refractory to RFCA and the early age of AAT onset ≤ 26.5 were able to predict the need for atrial appendectomy. No major complications occurred and 9 patients with tachycardia-induced cardiomyopathy were fully recovered. Long-term success was achieved in 98.0% of patients with multiple treatment managements. Conclusions: AAT originating from the distal AA were more refractory to RFCA. RFCA was the cornerstone of AAT catheter ablation. Video-assisted thoracoscopic atrial appendectomy was an effective strategy for those origins at the distal AA and the age of AAT onset ≤ 26.5. Ivabradine represented a promising treatment in treating AAT temporarily in pediatric and young adult patients.